Modern methods of determining the individual norm of volumes and premising intensity of the exercisable motor activity - Yaroslavna Puhach (Kharkiv State Academy of Physical Culture, 2020)
The problem of individual approach in the organization of physical activities always assumes need of accounting of the current functional state, the level of preparedness and according to it the choice of available physical activity on intensity and duration and also admissible complexity of its performance for the purpose of improving orientation of their use. All these criteria can be defined with success on condition of accounting of dynamics and individual norm of course by adaptation reaction to the offered physical activity. The tasks still remain insufficiently resolved in many ways that defined orientation of the stated results of the conducted researches. Purpose: determination of optimum volumes of load, its intensity, duration and admissibility of structure of the offered motive actions with the subsequent determination of nutrition state and rest sufficient for holding another training; determination of static stress providing a working pose necessary for the implementation of kinematic movements of parts of a body and dynamic efforts defining these movements. Material & Methods: high-speed video filming; assessment of static stress on bending angle of biokinematic links; method of pliometric loads; method of creation of semantic spaces for ordered submission of empirical data; method of assessment of qualitative structure of a somatotype according to M. Ya. Breitman and Ch. Hirata; geometrical methods of ordered structuring of the empirical data revealing regularities of responses of organism to alteration influences. Results: the consistent pattern of increment of size of lifting force on bending angle of knee joint is determined at control of change of static stress on bending angle of biokinematic couple "hip-shin". This pattern is expressed by a logarithmic spiral that is determined by the phylogenetic nature of morphofunctional dependence of dynamics of change of lifting force. Static stress is the most effective indicator of measure of exhaustion. The used standard pliometric exercises allow estimating an exhaustion measure for change of a way of damping of movement of body in a reaction phase with support at jumping off from the standard height. It is estimated on the basis of video filming of nature of movement of a supporting leg in a support phase in run or walking. The established exponential dependence allows determining the greatest possible volume of work and intensity of its performance in the current state of the individual by mathematical calculation. Such processing is carried out in real time. The technique is developed in KhSAPC. Conclusions: the presented methods of assessment of individual norm of optimum volume of physical activity and its intensity in actual scale become possible as a result of use of modern technical means of video filming and computer programs providing creation of animation structure of movement of an object. This technique has no analogs in the world in practice of researches in sport now.